Protocol for Clozapine Rechallenge in a Case of Clozapine-Induced Myocarditis. (July 2020) - Shivakumar, G.; Thomas, N.; Sollychin, M.; Takács, A.; Kolamunna, S.; Melgar, P.; Connally, F.; Neil, C.; Bousman, C.; Jayaram, M.; Pantelis, C.
Objective: Protocol for clozapine rechallenge in patients with a history of clozapine-induced myocarditis. Method: Clozapine-related cardiovascular adverse effects including myocarditis and cardiomyopathy have limited its widespread use in treatment-resistant schizophrenia. Here, we present a case of clozapine-induced myocarditis and successful cautious rechallenge. Ms. AA, a young female patient with severe psychosis developed myocarditis during her initial clozapine titration phase, which was thus discontinued. Subsequent response to other medications was poor, and she remained significantly disabled. We reviewed blood-based biomarkers identified during the emergence of her index episode of myocarditis and developed a successful clozapine rechallenge protocol, based on careful monitoring of changes in these indices and a very slow clozapine re-titration. Results and Conclusions: This protocol may have utility in the management of patients with a history of clozapine-induced myocarditis.